New Imidazo[2,1-b]naphtha[2,1-d][1,3]thiazole Derivatives: Synthesis, Antimicrobial and Antifungal Activity - Al-Lami, Naeemah (Iraqi Journal of Science, 2025)
A series of new derivatives of imidazo[2,1-b]naphtha[2,1-d][1,3]thiazole were synthesised, which they are substituted at position 2. Then, the new prepared imidazo thiazole derivatives were reacted with N,N-dimethyl formamide (DMF) and POCl3 to obtain new aldehyde derivatives at position 3. The new aldehyde derivatives underwent condensation reaction with the hydrazine afforded new hydrazone derivatives. The new compounds were characterized by spectra [IR, 1HNMR, 13CNMR, 2D NMR ( hsqc spectra)]. The synthesised compounds were examined the antimicrobial and antifungal activities, their antimicrobial activities against Escherichia coli, Streptococcus faecalis, Aeromonas hydrophila and Staphylococcus aureus were examined. Most of these compounds demonstrated antimicrobial activity. Interestingly, most of hydrazone derivatives showed antifungal activity towards spore germe and hyphae growth